2010
DOI: 10.1038/eye.2010.146
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes following Artisan aphakia iris claw lens implantation

Abstract: Objective To assess the visual outcome of eyes undergoing Artisan lens implantation for aphakia, to identify reasons for poor outcomes, and to report incidences of post-operative uveitis, glaucoma, or hyphaema. Methods A retrospective analysis of 32 eyes rendered aphakic through various causes, which subsequently underwent Artisan lens implantation. Results A total of 32 eyes from 31 patients were reviewed. Follow-up ranged from 6 to 42 months, mean 17.3 months. The commonest cause of aphakia was following com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 14 publications
(14 reference statements)
5
25
0
Order By: Relevance
“…This is comparable to the results in previous studies of PC iris-claw IOLs, 21 anterior-fixated iris-claw IOLs, 22,23 secondary open-loop AC IOLs (60% to 77% of eyes 11,24 ), secondary sulcus-sutured PC IOLs (53.8% to 77.8% 3,14 ), and secondary iris-sutured PC IOLs (60% to 67% 8,25 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is comparable to the results in previous studies of PC iris-claw IOLs, 21 anterior-fixated iris-claw IOLs, 22,23 secondary open-loop AC IOLs (60% to 77% of eyes 11,24 ), secondary sulcus-sutured PC IOLs (53.8% to 77.8% 3,14 ), and secondary iris-sutured PC IOLs (60% to 67% 8,25 ).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies 11,18,22 found that secondary AC IOL implantation can result in severe endothelial cell loss and subsequent corneal decompensation. G€ uell et al 26 report a 7.78% cell loss within the first year and a 10.9% loss over the first 36 months after anterior-fixated aphakic Artisan IOL implantation, suggesting that most endothelial cell damage occurs intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…The Artisan IOL (Ophtec BV), a poly(methyl methacrylate) (PMMA) iris-fixated IOL, has a better design than previous generations and has been successfully used to correct aphakia 5,[9][10][11][12][13] and high myopia 1,14,15 in many countries.…”
mentioning
confidence: 99%
“…From personal communication, A it is my understanding that Budo's experience with the iris-fixated IOL has proven safe and effective for pseudophakic correction. 2,3 Robert P. Lehmann, MD Nacogdoches, Texas, USA…”
mentioning
confidence: 98%